Az ehető rovarok szerepe a vízi állatok fenntartható és környezetbarát takarmányozásában: Irodalmi áttekintés - Hancz, Csaba (Acta Agraria Kaposváriensis, 2024)
To ensure sustainable growth, feed-fed aquaculture needs to reduce its reliance on fishmeal and oil. Introducing of novel aquaculture feeds such as macroalgae, bacteria, yeasts, and insects can greatly reduce the need for fish in aquaculture while maintaining efficiency and omega-3 fatty acid profiles. Insects, particularly, can efficiently convert organic waste into valuable products, thus reducing waste management costs and replacing fish and soybean meal. The flexibility and efficiency of insect metabolism contribute to their potential in mass food and feed production. However, for insect farming to have a global impact, it needs to be economically viable and capable of supplying insect products in industrial quantities. Extensive research has been conducted to explore the potential of insect meal for various physiological effects in important crustacean and fish species in aquaculture. This paper aims to summarize the relevant literature on these topics and highlight the results of experiments conducted with key species.
Keywords: ehető rovarok; takarmányozás; akvakultúra; fenntarthatóság